Intervensi Masyarakat Suku Laut oleh Tokoh Agama di Kepulauan Riau - Marisa Elsera; Nanik Rahmawati; Annisa Valentina (Indonesian Center for Religion and Society Studies (InTReSt), 2022)
The Sea Tribe is one of the indigenous peoples who are still isolated in the Riau Archipelago. The lifestyle, which is very simple in all aspects, makes the Sea Tribe far from the level of welfare. In order to improve their standard of living, traditional and religious leaders have emerged who accompany people who are classified as closed. The roles and functions of these community leaders are seen in the development of the sea tribe. Qualitative research method with a descriptive approach. Data obtained through structured interviews with interview and observation guidelines and documentation. The selection of informants using purposive sampling technique. The data analysis technique is data reduction from the results of interviews with marine tribal communities then presenting the data presented in the form of narrative descriptions, as well as verification or drawing conclusions. The results of the study found that religious leaders were quite successful in carrying out social interventions in the form of spreading religious teachings to the Sea Tribe community, acting as motivators, religious leaders providing guidance and consultation, religious leaders helping empower the Sea Tribe community. As change agents, religious leaders provide assistance and socialization in spiritual, social, administrative, economic and health aspects. As a target of change, the sea tribes opened themselves to the assistance provided by these religious leaders.